1978
DOI: 10.1161/01.cir.57.6.1058
|View full text |Cite
|
Sign up to set email alerts
|

Nonuniform cardiac sympathetic nerve discharge: mechanism for coronary occlusion and digitalis-induced arrhythmia.

Abstract: This study examined nonuniform postganglionic cardiac sympathetic neural discharge as a possible mechanism involved in the production of coronary occlusion or ouabain-induced arrhythmias. After acute occlusion of the left anterior descending coronary artery in 12 cats, anesthetized with alpha-chloralose and pretreated with atropine, arrhythmia occurred within 3 min in eight animals; three of these died in ventricular fibrillation. In recordings from 15 nerves in the eight animals with arrhythmia, spontaneous d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1983
1983
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…Thus, the shortening of ERP in response to coronary occlusion may well be accounted for if efferent sympathetic discharge to the heart was increased. Coronary occlusion has been reported to produce increases in both sympathetic afferent and efferent activities (BROWN, 1967;FELDER and THAMES, 1979;GILLIS, 1971;LATHERS et al, 1978;MALLIANI et al, 1969;UCHIDA and MURAO, 1974;WEAVER et a1.,1981). In spinal cats, MALLIANI et al (1969) reported an increase in efferent sympathetic output to the heart during coronary occlusion and proposed a cardiocardiac sympathetic reflex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the shortening of ERP in response to coronary occlusion may well be accounted for if efferent sympathetic discharge to the heart was increased. Coronary occlusion has been reported to produce increases in both sympathetic afferent and efferent activities (BROWN, 1967;FELDER and THAMES, 1979;GILLIS, 1971;LATHERS et al, 1978;MALLIANI et al, 1969;UCHIDA and MURAO, 1974;WEAVER et a1.,1981). In spinal cats, MALLIANI et al (1969) reported an increase in efferent sympathetic output to the heart during coronary occlusion and proposed a cardiocardiac sympathetic reflex.…”
Section: Discussionmentioning
confidence: 99%
“…Only recently, however, have attempts been made to correlate these changes in ventricular refractoriness with autonomic reflexes mechanisms (BLAIR et a!.,1980;LATHERS et a!.,1978;MARTINS, 1981). In a study on anesthetized cats, BLAIR et al (1980) demonstrated that the stimulation of the central end of the cut caudocagal nerve produced significant alterations in the left ventricular refractory period.…”
mentioning
confidence: 99%
“…Adult male Wistar rats (n=20, 220-280 g) were housed under standard controlled conditions (7:00 a.m./7:00 p.m. light/ dark cycle; [20][21][22] o C; 45-55% humidity) with food and water ad libitum. Rats were divided randomly into two groups: (A) rats with epilepsy (n=10), (B) rats with epilepsy that received a daily dose of 3.0 g kg -1 of a 30% ethanol solution via an oesophagic probe for 30 days (n=10).…”
Section: Methodsmentioning
confidence: 99%
“…A toxic dose of deslanoside increased the concentration of a noradrenaline metabolite, and midcollicular decerebration increased the deslanoside dose required to produce ventricular arrhythmias (Helke et al, 1979). Similarly, the dose of ouabain needed to produce ventricular arrhythmias in cats increased two weeks after sympathectomy (Lather et al, 1978). Lechat & Schmitt (1982) reported that the dose of digitalis glycoside required to produce ventricular arrhythmias was reduced by Yoh, an a2-adrenoceptor antagonist.…”
Section: Electrophysiological Effects Of Digitalis On the Heartmentioning
confidence: 98%
“…Pretreatment of animals with reserpine, fl-adrenoceptor blocking agents, al-adrenoceptor antagonists, a2-adrenoceptor agonists, anticholinoceptor agents, ganglionic blocking agents and dopamine receptor agonists have been shown to increase the dose of digitalis required to produce cardiac arrhythmias (Lather et al, 1978;Helke et al, 1979).…”
Section: Introductionmentioning
confidence: 99%